A Trauma-Informed Approach to Peer Physical Examination - Sadie Elisseou; Emily Adams; Maya Adler (Association of American Medical Colleges, 2022)
Introduction The majority of medical schools utilize peer physical examination (PPE) as a teaching tool. In recent years, trauma-informed care (TIC) has been applied as a framework for physical examination to prevent patient retraumatization. Although medical students experience rates of trauma comparable to those of the general population, trauma-informed principles have not been integrated into PPE curricula. Methods We created a novel trauma-informed PPE (TIPPE) curriculum grounded in core principles of TIC for first-year medical students. Perceptions of safety, trust, and autonomy in PPE practice were compared between the 152 students participating in the TIPPE curriculum and a control group from the prior year. Results Twenty-nine percent of the 42 first-year medical student respondents in our sample endorsed a prior diagnosis with a mental health condition, and 33% endorsed a trauma history. Approximately 5% of student respondents (n = 5) in the interventional and control groups reported that PPE triggered recall of a prior traumatic event. Following participation in the TIPPE curriculum, familiarity with TIC principles rose significantly, although overall rating of the experience did not change. Thematic analysis of qualitative data highlighted students' desire for earlier and increased inclusion of TIC principles in the curriculum. Discussion Our results demonstrate the necessity of adapting the standard PPE model in medical education in response to the real risk of student retraumatization. In sharing our curriculum, associated resources, and student-derived suggestions for further improvement, we provide a blueprint for other institutions seeking to train trauma-informed clinicians.